Structural Regulation and Support Coupling Effect of Single‐Atom Catalysts for Heterogeneous Catalysis - Liu, Daobin; He, Qun; Ding, Shiqing; Song, Li (Advanced energy materials, 2020)
Single atom catalysts (SACs) that integrate the merits of homogeneous and heterogeneous catalysts have been attracting considerable attention in recent years. The individual metal atoms of SACs can be stabilized on supports through various unsaturated chemical sites or space confinement for achieving the maximized atom utilization efficiency. Aside from the development of strategies for preparing high loading and high purity SACs, another key challenge in this field is precisely manipulating the geometric and electronic structure of catalytically active single metal sites, thus rendering the catalysts exceptionally reactive, selective, and stabile compared to their bulk counterparts. This review summarizes recent advancements in SACs for heterogeneous catalysis from the perspective of local structural regulation and the synergistic coupling effect between metal species and supports. Special emphasis is placed on the elucidation of the catalytic structure‐performance relationship in terms of coordination environment, valence state and metal‐support interactions by advanced characterization and theoretical studies. Select in situ or operando characterization techniques for tracking the SACs’ structure evolution under realistic conditions are highlighted. Finally, the challenges and opportunities are discussed to offer insight into the rational design of more intriguing SACs with high activity and distinct chemoselectivity. Single atom catalysts have emerged as a new frontier due to almost 100% atom utilization efficiency along with outstanding catalytic performance. This review highlights the recent advancements in tailoring local structure and metal‐support interaction of single atom catalysts to gain a deeper insight into the structure‐performance relationship. The challenges and opportunities in this field are further discussed.